Effect of rhizobial inoculation on growth of Calliandra tree species under nursery conditions - Lesueur, Didier; Founoune, H; Lebonvallet, S; Sarr, A (Springer, 2010)
A nursery experiment was conducted in un-sterilized soil in Senegal using six Calliandra species or provenances inoculated with a mixture of seven rhizobial strains. Plant growth was assessed periodically at 1, 2, 3, 12 and 18 months whereas nodulation, shoot and root dry weights were assessed at 12 and 18 months after planting (MAP). Un-inoculated seedlings of all the six species died at 12 months after planting. Results of growth assessments were variable with significant differences (P < 0.05) between C. calothyrsus Meissn provenances (Flores and San Ramón) and C. juzepczukii Standley in height at 1, 2 and 3 MAP. Shoot dry weights of San Ramón provenance of C. calothyrsus Meissn were also significantly different from those of C. acapulcensis (Britton and Rose) Standley and C. longepedicellata (Mc Vaugh) H. Hern and Macqueen at 18 MAP. In contrast, C. glandiflora (L’Her.) Benth grew poorly and did not nodulate. Although rhizobial inoculation improved shoot and root dry weights some differences were observed among the Calliandra species in response to the inoculation, which suggested the occurrence of interaction between the rhizobial strains and the host plant species tested.